Effect of honey as natural preservative on total aerobic plate count (APC) of fresh ground chicken meat stored under refrigerator conditon - Naresh R Ravi (2016)
A preliminary study was conducted with the aim of determining the effect of honey as natural preservative on aerobic plate count (APC) of fresh ground chicken meat stored under aerobic condition at refrigerator temperature (4±°C) . Two types of honey which were raw kelulut honey and commercial Giant honey used in this experiment. Results shows that there was signiﬁcant difference (P <0.05) among the treatments on total APC. Besides that, there was also a signiﬁcant difference (P <0.05) observed in the interaction between treatment and days. From the ﬁndings, both raw kelulut honey and commercial giant honey were able to delay the growth of bacteria in ground chicken meat during the aerobic storage at refrigerator temperature compared with experimental control. However, only raw kelulut honey was found to be most effective in inhibiting the bacteria growth with the least mean (5.218 log CF U/g) compare with commercial Giant honey (5.714 log CFU/g). ln addition, kelulut honey was reported to extend the shelf life of ground chicken meat to 10 days based on total APC storing under aerobic storage at refrigerator temperature compared with giant honey which is only seven days. This study also demonstrated that bacteria load was signiﬁcantly increased with the increase of storage period regardless of treatment used to preserve ground chicken under refrigerator condition.